2021
DOI: 10.1002/er.6539
|View full text |Cite
|
Sign up to set email alerts
|

Classification and prediction of gas turbine gas path degradation based on deep neural networks

Abstract: Summary This paper mainly analyzes the performance degradation of turbomachinery in gas turbines, classifies the main types of degradation: increased tip clearance, corrosion/wear, fouling, and multiple degradation, and predicts the degradation trend through deep neural networks. The deep feedforward neural network is used to build the regression model and two classification models. The regression model uses a back propagation algorithm optimized by Lenvenberg Marquardt to convert the efficiency and flow capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Supporting this observation, Table 2 presents the evaluation parameter values for both the training and testing data, with the training data showing a lower RMSE value, aligning with the anticipated outcomes. The fact that these numbers are less than 0.5 shows the better per formance of this model than other research with the same purpose [21,30,39,40]. Upon comparing the two outcomes, it was found that the accuracy of the model is better for the training data than the testing data.…”
Section: Resultsmentioning
confidence: 75%
“…Supporting this observation, Table 2 presents the evaluation parameter values for both the training and testing data, with the training data showing a lower RMSE value, aligning with the anticipated outcomes. The fact that these numbers are less than 0.5 shows the better per formance of this model than other research with the same purpose [21,30,39,40]. Upon comparing the two outcomes, it was found that the accuracy of the model is better for the training data than the testing data.…”
Section: Resultsmentioning
confidence: 75%
“…The results of the proposed NARX model validated the capability of the NARX NN in determining the dynamic behavior of the gas turbine system, with a simulation MSE of 3.8414 × 10 −3 for the high pressure (HP) turbine, 1.29152 × 10 −1 and 2.12090 × 10 −4 for the gas and air control valves, respectively. In terms of deep learning, Cao et al (2021) [18] have presented different deep learning techniques that have been used to predict the changes in the efficiency and flow capacity of turbomachinery. The degradation predictions have been established via the LSTM approach, with a high accuracy ranging from 81.65% to 93.65%.…”
Section: Related Work and The Paper Contributionmentioning
confidence: 99%
“…In recent years, the gas turbine-combined cycle (GTCC) has become increasingly popular in the power industry for its high efficiency and low pollutant emissions [1][2][3]. The GTCCs are more frequently used for peak shaving applications in some countries, for example, in China, requiring GTCCs to operate for a considerable period under part-load conditions.…”
Section: Introductionmentioning
confidence: 99%